2005
DOI: 10.1111/j.1365-4632.2004.02574.x
|View full text |Cite
|
Sign up to set email alerts
|

Lupus erythematosus tumidus: a series of 26 cases

Abstract: No inflexible histologic criteria should be employed for the diagnosis of LET. This subset of lupus erythematosus is characterized by intense photosensitivity, definite clinical lesions, a benign course, the absence of systemic disease, good response to antimalarial treatment, and a tendency to recur. More studies should be performed in order to establish the true incidence of LET because this subset of CCLE is probably underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
57
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 19 publications
(51 reference statements)
9
57
0
7
Order By: Relevance
“…However, in a recent report by Vieira et al, 16 histologic reclassification, only a slight epidermal atrophy histologic persisted as a potential histologic criterion for separating the two conditions. Thus, although a difference between two clinical pictures seems to have been accepted in the minds of physicians, our findings support a broader but single histopathologiceclinical spectrum rather than two distinct entities.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, in a recent report by Vieira et al, 16 histologic reclassification, only a slight epidermal atrophy histologic persisted as a potential histologic criterion for separating the two conditions. Thus, although a difference between two clinical pictures seems to have been accepted in the minds of physicians, our findings support a broader but single histopathologiceclinical spectrum rather than two distinct entities.…”
Section: Discussionmentioning
confidence: 88%
“…In our series, the rarity of high-titer antinuclear antibodies in either group, the absence of positive lupus band test results in JLIS, and their irregular positivity in LET are in accordance with the literature. 2,3,13,[16][17][18] After reclassification of patients based on blinded histologic review, the clinical differences were almost totally erased. However, before or after the reclassification, the extent to which JLIS and LET share numerous characteristics is striking, especially for age at onset, photosensitivity, response to antimalarial drugs, lack of extracutaneous involvement, and histologic findings (CD20 expression, presence of mucin).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our patient and another one, the skin lesion was reproduced by provocative phototesting; however, such testing was not performed in the other eight patients. Vieira et al [17] reported finding a distinct relationship between disease progression and solar exposure in 16 of 26 patients (62%) studied, while they were unable to determine any relationship from the medical histories of the remaining cases studied. These researchers found that the interval between sun exposure and the development of an eruption Perivascular and periadnexal lymphocytic infiltration without alternation of the dermo-epidermal junction was less than 2 weeks.…”
Section: Discussionmentioning
confidence: 92%
“…LET is a rare form of chronic cutaneous lupus erythematosus that characteristically presents with succulent plaques with a reddish or violaceous smooth surface. In correlation with characteristic histological and laboratory findings, patient photosensitivity, and a response to antimalarials, this diagnosis can be made [1][2][3].…”
mentioning
confidence: 99%